Persepsi Literasi Digital Mahasiswa Calon Guru IAIN Palopo - Muh Yamin; Nur Fakhrunnisaa (SAP (Susunan Artikel Pendidikan), 2022)
The process of holding education in the digital era presents its own challenges, especially for prospective teacher students, who not only have to master four basic competencies, namely pedagogic competence, professional competence, social competence, and personality competence, but also they are required to have digital literacy or mastery of technology and information competence. This study aims to measure the perception of digital literacy of prospective teacher students based on the four aspects of digital literacy competence proposed by Gilster, including aspects of internet searching, hypertext navigation, content evaluation, and knowledge assemblies. The method of this research was quantitative descriptive using survey method and purposive sampling technique with descriptive analysis, held on May-June 2022, the number of respondents was 436 students from the Tarbiyah faculty of IAIN Palopo. The results of the study illustrates that the perception of digital literacy of prospective teacher students of IAIN Palopo was in the high category. This research contributes in the form of information to the academic community related to the literacy level of prospective teacher students.